Robot and working tube-assisted invasion-controlled surgery for spinal metastases - Zhou, Shangbin; Li, Bo; Wang, Pengru; Xu, Meiling; Zhao, Jian; Duan, Shujie; Zhu, Zhipeng; Xu, Wei; Xiao, Jianru (Frontiers in Surgery, 2023)
Objective. This study was to introduce the robot and working tube assisted minimally invasive surgery for spinal metastases. And to elaborate on the concept of invasion-controlled surgery (ICS). Summary of Background. many patients with spinal metastasis cancer cannot afford serious complications when undergoing traditional open surgery because of poor physical condition. Robot and minimally invasive technology have been introduced into the field of spine surgery and they have shown good advantages. Methods. Six patients who underwent robot and working tube assisted ICS for spinal metastases. Relevant demographic, medical, surgical, and postoperative information were collected from medical records and analyzed. Results. Mean operative time was 3.8 hours and mean length of the surgical incision was 4.9 cm. Mean estimated blood loss was 400 ml. The mean bedtime and hospital length of stay respectively was 3.2 days and 6.5 days. No obvious complications were reported during treatment. The mean accuracy of screw placement was 98%. The mean time for further system treatment after surgery was 5.8 days. All patients experienced significant pain relief. The mean preoperative visual analogue scale (VAS) was 7.83 points. The mean VAS at 1 day, 1 week, and 1 month after surgery was 2.83, 1.83 and 1.17 points, respectively. Frankel grade was improved in five of six patients. One patient preoperatively with Frankel grade D was the same postoperatively. Conclusion. The concept of ICS is suitable when patients with spinal metastases. Robot and working tube assisted ICS for spinal metastases is one of the safe and effective treatment method.